The hermeneutics of tradition : explorations and examinations - Hovey, Craig, 1974-; Olsen, Cyrus P. (Eugene, Oregon : Cascade, 2014)
The Hermeneutics of Tradition presents the latest scholarship on tradition as a concept and reality in the development of Christian cultures. One aim is to show that traditions are upheld, communicated, and developed within a recognizable set of interpretive guidelines (or rules) and that analysis of these sets both requires and reveals a "hermeneutics of tradition" The work of the authors included here presents the precarious integrity of traditions and the often tenuous hold upon those traditions exercised by the hermeneutics that drive dynamics of preservation and change. As scholars and religious worshippers continue ancient traditions of receiving strangers with generous hospitality, the coherence of tradition serves conversations about where our true differences lie.
Up the mountain with the Fathers : evangelical ressourcement of early Christian doctrine / Hans Boersma -- Communion and catholicity / Nyssa, Augustine, Aquinas / C. C. Pecknold -- The hermeneutics of schism and the question of "sister churches" / Will T. Cohen -- The holiness of the church in north African theology / J. Patout Burns Jr. -- Martin Luther's hermeneutics of Christ's deified flesh / Adam G. Cooper -- Alasdair MacIntyre's hermeneutics of tradition / Craig Hovey -- Tradition, truth, and time : remarks on the "liturgical action" of the church / Robert C. Koerpel -- Joseph Ratzinger and the hermeneutic of continuity / Tracey Rowland -- The wound of tradition / Jonathan Tran
Includes bibliographical references.
Description based on online resource; title from PDF title page (EBSCO, viewed February 25, 2015).
Keywords: Tradition (Theology); Hermeneutics; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books